2004
DOI: 10.1002/chin.200440128
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Imidazolinium Salts Derived from (L)‐Valine. Investigation of Their Potential in Chiral Molecular Recognition.

Abstract: Recognition. -Several imidazolium salts are synthesized from (L)-valine. It is found that the choice of counter anion is crucial for the properties of the salt. For example, NTf2 anion leads to room temperature ionic liquids, while the PF6 anion only gives solid salts. -(CLAVIER, H.; BOULANGER, L.; AUDIC, N.; TOUPET, L.; MAUDUIT*, M.; GUILLEMIN*, J.-C.; Chem. Commun. (Cambridge) 2004, 10, 1224-1225; Inst. Chim., CNRS, Univ. Rennes, F-35042 Rennes, Fr.; Eng.) -M. Paetzel 40-128

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…9 Influence of the aryl substituent on the chiral discrimination: 1 H spectra (400 MHz, CD 2 Cl 2 ) of (rac)-Mosher salt in imidazolinium 11 (a) and 12 (b) in presence of crown ether 18C 6 . Adapted from [94] In another study, the presence of a second hydroxyl group in the cation structure further improved diastereomeric interaction as shown by the bidentate imidazolium CILs reported by Wilhelm et al [95]. When enantiopure CIL 13 with a BF 4 − counteranion was used in combination with Mosher's salt, no signal splitting was obtained in either the 1 H NMR or the 19 F NMR spectra (Scheme 6).…”
Section: Chiral Discrimination Using Cils In Nmr Spectroscopymentioning
confidence: 85%
See 1 more Smart Citation
“…9 Influence of the aryl substituent on the chiral discrimination: 1 H spectra (400 MHz, CD 2 Cl 2 ) of (rac)-Mosher salt in imidazolinium 11 (a) and 12 (b) in presence of crown ether 18C 6 . Adapted from [94] In another study, the presence of a second hydroxyl group in the cation structure further improved diastereomeric interaction as shown by the bidentate imidazolium CILs reported by Wilhelm et al [95]. When enantiopure CIL 13 with a BF 4 − counteranion was used in combination with Mosher's salt, no signal splitting was obtained in either the 1 H NMR or the 19 F NMR spectra (Scheme 6).…”
Section: Chiral Discrimination Using Cils In Nmr Spectroscopymentioning
confidence: 85%
“…In 2004, Guillemin et al reported even greater splitting up to 63 Hz in 19 F NMR and 60 Hz in 1 H NMR spectroscopy using the valine-derived CILs (11 and 12) [94]. They modified the 19 F NMR protocol developed by Wassercheid and coworkers [92] by using the potassium Mosher's salt instead of the sodium salt and recorded NMR spectra in deuterated acetone.…”
Section: Chiral Discrimination Using Cils In Nmr Spectroscopymentioning
confidence: 97%
“…More interestingly, the predominant hydrogen bonding interaction between the anion and heteroatom were validated through X-ray diffraction study and computational study. To date, CILs, especially derived from natural amino acids, are employed in asymmetric synthesis [38][39][40][41], spectroscopic analysis (NMR, fluorescence spectrum) [42][43][44][45][46][47], and chromatography (GC, HPLC, CCC, and CE) [48][49][50][51][52][53][54][55]. CILs exhibited good chiral discrimination capabilities.…”
Section: Tsils For Chiral Resolutionmentioning
confidence: 99%
“…45 The 18C6 was added to increase the solubility of potassium Mosher's salt in chloroform-d 1 by forming a complex between potassium and crown ether. 46 For 19 F-NMR analysis, a fivefold molar excess of respective PCIL with regard to potassium Mosher's salt was dissolved in 0.5 ml of the feedstock solution.…”
Section: Enantiomeric Recognition Studies Of Pcils Towardmentioning
confidence: 99%